The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5005/jp-journals-10024-2432
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Genotoxic effect on the Buccal Mucosa Cells of Patients Undergoing Fixed Orthodontic Treatment

Abstract: Aim:To evaluate the presence of metal ions and deoxyribonucleic acid damage on the cells of buccal mucosa in subjects scheduled to undergo fixed orthodontic treatment. Materials and methods:Eighty patients scheduled to undergo orthodontic treatment were included in the present study. Samples were collected from buccal mucosa of the subjects at five different intervals: before the starting of the fixed appliance therapy, 5 months after the insertion of the appliance, 10 months after insertion of the appliance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…For example, Faccioni et al demonstrated DNA damage in oral mucosa cells in patients undergoing orthodontic treatment (14,15). Others also detected DNA damage in oral mucosal cells as a result of metals released by orthodontic devices in the oral cavity (16,17). However, Westhphalen et al were not able to detect genetic damage in oral mucosal cells following orthodontic therapy (18).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Faccioni et al demonstrated DNA damage in oral mucosa cells in patients undergoing orthodontic treatment (14,15). Others also detected DNA damage in oral mucosal cells as a result of metals released by orthodontic devices in the oral cavity (16,17). However, Westhphalen et al were not able to detect genetic damage in oral mucosal cells following orthodontic therapy (18).…”
Section: Resultsmentioning
confidence: 99%
“…Due to this long contact time, conventional braces can cause changes in DNA. A study by Kapadia et al [38] showed that due to the content of metal ions, fixed orthodontic appliances reduce cell viability by altering DNA and promoting the process of apoptosis. Another category of orthodontic appliances is polycarbonate-based orthodontic brackets.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 ] Orthodontic appliances may release amounts of metal ions;[ 5 6 7 8 9 10 ] this can lead to diverse toxic effects such as DNA damages and oral lesions. [ 11 12 ] Some studies have already shown the release of metal ions into saliva and the cytotoxicity and genotoxicity of silver solder in oral cells. [ 13 14 15 16 17 ] In addition to the metallic elements of stainless steel, such as nickel (Ni), chromium (Cr), and iron (Fe), silver solder alloys contain silver (Ag), copper (Cu), and zinc (Zn).…”
Section: Introductionmentioning
confidence: 99%